A narrative review on teacher professional ethics in Malaysia - Wan Yusoff, Wan Mazwati; Salleh, Sakinah (JPPW, 2021)
The aim of this narrative review was to summarise and synthesize research reports pertaining to teacher professional ethics in Malaysia. It began with a broad search criterion to include as many researches as possible. Twenty nine articles met the selection criteria and were reviewed and grouped according to emerging themes. The results revealed that most studies were done to measure the level of knowledge and practices of professional ethics among in-service and pre-service teachers in Malaysia followed by measuring the interactions between all constructs of teacher professional ethics; and the relationship with students’ moral behaviour. Fewer studies were conducted to find out the dimensions of professional ethics and how values and ethics were inculcated in both teachers and students. However, the vastness of what transpired in the real settings could not be explained by the few researches that had already been done. This study found a huge gap between insights provided by those reviewed articles and reality on the ground. The review identified common methodological mistakes committed which compromised the validity and generalizability of the findings. Gaps in literature on teacher professional ethics were identified and disseminated to inform further research.